Antimicrobial tanzawaic acid derivatives from the endophytic Penicillium citrinum BCC71086. (29th January 2022) - Dramae, Aibrohim; Intaraudom, Chakapong; Bunbamrung, Nantiya; Boonyuen, Nattawut; Auncharoen, Patchanee; Pittayakhajonwut, Pattama
Abstract: Seven previously undescribed compounds including five tanzawaic acid analogues [named 10-hydroxytanzawaic acid U (1 ), 10-hydroxytanzawaic acid Q (2 ), 10-hydroxytanzawaic acid T (8 ), tanzawaic acids Z1 (9 ) and Z2 (11 )], 7-methoxy-2, 5-dimethyl-2, 3-dihydrobenzofuran-6-ol (15 ), and (1 S, 3 R )-1, 8-dimethoxy-3, 5-dimethyl-6-hydroxy isochroman (17 ) along with fifteen known compounds were isolated from the endophytic fungus, Penicillium citrinum BCC71086. The absolute stereochemistry of tanzawaic acid derivatives were verified by modified Mosher's method together with NOESY spectral information. The isolated compounds were evaluated for antimicrobial activity as well as cytotoxicity against both cancerous (MCF-7 and NCI–H187) and non-cancerous (Vero) cells. Tanzawaic acids possessed broad spectrum of antimicrobial activity without significant cytotoxicity. In addition, among these isolated compounds, the unknown dihydrobenzofuran 15 had the strongest antimalarial activity with IC50 value of 3.76 μΜ. All tested compounds also possessed antitubercular activity with MIC values in a range of 6.25–25.0 μg/mL. Graphical abstract: Image 1 Highlights: Five unknown tanzawaic acid analogues were isolated from the endophytic Penicillium citrinum BCC71086. Absolute configurations were verified by using Mosher's method together with NOESY data. The isolated compounds were assessed for biological activity as well as cytotoxicity. Tanzawaic acid derivatives exhibited antimicrobial activity without significant cytotoxicity.